Automatic Table Distillation Column - Ružička, Michal (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
Main goal of this project was construction of small autonomous distillation column.It should serve as an example of potential uses of electrotechnics for general public. The column willhave compact design based on Arduino board. It will contain everything necessary for its function,and will be operable even by layman. Part of the project is also closed cooling system based on Peltiermodules.
Keywords: distillation; Arduino; cooling; peltier; automation